2006
DOI: 10.1002/ana.21007
|View full text |Cite
|
Sign up to set email alerts
|

Block of neural Kv1.1 potassium channels for neuroinflammatory disease therapy

Abstract: Kv1.1 blockade may target neurons and astrocytes, and modulate neuronal activity and neural cell volume, which may partly account for the attenuation of the neurological deficits. We propose that Kv1.1 blockade has a broad therapeutic potential in neuroinflammatory diseases (multiple sclerosis, stroke, and trauma).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Additionally, a simulation with mutant-urotoxin (Lys25Ala) indicated that Lys25 does not have the same role in the binding of urotoxin to hK v 1.2 as in other a-KTx-6 toxins. Our results suggest that urotoxin may be useful as a pharmacologic tool to reveal the physiologic function of hK v 1.2 channels in in vitro and in vivo experiments, as a lead for peptidomimetics for the targeting of hK v 1.2 channels, and as an experimental therapeutic tool to restore axonal conduction in demyelinated axons, where inhibition of K 1 channels has beneficial effects (Beraud et al, 2006;Shi and Sun, 2011).…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, a simulation with mutant-urotoxin (Lys25Ala) indicated that Lys25 does not have the same role in the binding of urotoxin to hK v 1.2 as in other a-KTx-6 toxins. Our results suggest that urotoxin may be useful as a pharmacologic tool to reveal the physiologic function of hK v 1.2 channels in in vitro and in vivo experiments, as a lead for peptidomimetics for the targeting of hK v 1.2 channels, and as an experimental therapeutic tool to restore axonal conduction in demyelinated axons, where inhibition of K 1 channels has beneficial effects (Beraud et al, 2006;Shi and Sun, 2011).…”
Section: Introductionmentioning
confidence: 87%
“…Demyelination induces alterations in K + channel expression and distribution, as there is an upregula- currents lead to an intracellular potassium depletion that is assumed to be a first step in apoptotic cascades as it triggers water loss and disinhibition of intracellular proapoptotic enzymes [61]. Administration of a K v 1.1 selective blocker (BgK-F6A) ameliorates disease course in EAE mice while it did not affect T cell activation [62]. In vivo relevance of TASK channels on T lymphocytes was addressed by pre-treatment of myelin basic protein-specific encephalitogenic T lymphocytes with a TASK1 modulator (anandamide) which was associated with significant amelioration of the disease course in Lewis rats [15].…”
Section: Voltage-gated and K 2p Potassium Channelsmentioning
confidence: 99%
“…Some studies suggest that specific potassium channels may have feedback loops with cytokine and other immune system response mechanisms, therefore by suppressing these channels, the cell may not face autoimmune attack [3]. Other studies suggest that potassium channel blockers may enhance CNS motor evoke brain activation to improve symptoms of demyelination, but have no effect on motor conduction [20].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Ion channel blockers are becoming a common treatment for Multiple Sclerosis, and other neural diseases [3]. If the effects of a therapy on myelin capacitance, conductance or ion channel permeability are known, the model presented can quickly be modified to test whether the therapy could alleviate symptoms of slowed conduction velocity.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation